Category theorem on contingencies of hypersurfaces in Euclidean space - Ilmuradov, D. D. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
A thorough investigation of the characteristic of contingency of a second-category set in ℝ^m+1 is presented. In particular, the graph of a Lipschitz function is studied.